Impact of d-Band Occupancy and Lattice Contraction on Selective Hydrogen Production from Formic Acid in the Bimetallic Pd3M (M = Early Transition 3d Metals) Catalysts - Lee, Sangheon; Cho, Jinwon; Jang, Jong Hyun; Han, Jonghee; Yoon, Sung Pil; Nam, Suk Woo; Lim, Tae Hoon; Ham, Hyung Chul (AMER CHEMICAL SOC, 2016)
Catalysts that are highly selective and active for H-2 production from HCOOH decomposition are indispensable to realize HCOOH-based hydrogen storage and distribution. In this study, we identify two effective routes to promoting the Pd catalyst for selective H-2 production from HCOOH by investigating the effects of early transition metals (Sc, Ti, V, and Cr) incorporated into the Pd core using density functional theory calculations. First, the asymmetric modification of the Pd surface electronic structure (d(z)(2) vs d(yz) + d(zx)) can be an effective route to accelerating the H-2 production rate. Significant charge transfer from the subsurface Sc atom to the surface Pd atom and subsequent extremely low level of d band occupancy (<0.1) around the Sc atoms are identified as a key factor in deriving the asymmetric modification of the Pd surface electronic structure. Second, in-plane lattice contraction of the Pd surface can be an effective route to suppressing the CO production. Compressive strain of the Pd surface is maximized as a result of alloying with V and induces subsequent changes in adsorption site preference of the key intermediates for the CO production path, resulting in a significant increase in the activation energy barrier for the CO production path. The unraveled atomic-scale factors underlying the promotion of the Pd surface catalytic properties provide useful insights into the efforts to overcome limitations of current catalyst technologies in making the HCOOH-based H-2 storage and distribution economically feasible.
Keywords: FUEL-CELL; DECOMPOSITION; PALLADIUM; SURFACES; ELECTROOXIDATION; REACTIVITY; OXIDATION; DEHYDROGENATION; NANOPARTICLES; GENERATION